Liming reduces soil phosphorus availability but promotes yield and P uptake in a double rice cropping system - Ping LIAO; Mart B.H. ROS; Natasja VAN GESTEL; Yan-ni SUN; Jun ZHANG; Shan HUANG; Yong-jun ZENG; Zi-ming WU; Kees Jan VAN GROENIGEN (Journal of Integrative Agriculture, 2020)
Liming is often applied to alleviate soil acidification and increase crop yield on acidic soils, but its effect on soil phosphorus (P) availability is unclear, particularly in rice paddies. The objective of this study was to examine the effect of liming on rice production, yield and P uptake in a three-year field experiment in a double rice cropping system in subtropical China. We also conducted an incubation experiment to investigate the direct effect of liming on soil available P and phosphatase activities on paddy soils in the absence of plants. In the incubation experiment, liming reduced soil P availability (measured as Olsen-extractable P) by 14–17% and inhibited the activity of soil acid phosphatase. Nonetheless, lime application increased grain yield, biomass, and P uptake in the field. Liming increased grain yield and P uptake more strongly for late rice (26 and 21%, respectively) than for early rice (15 and 8%, respectively). Liming reduced the concentration of soil available P in the field as well, reflecting the increase in rice P uptake and the direct negative effect of liming on soil P availability. Taken together, these results suggest that by stimulating rice growth, liming can overcome direct negative effects on soil P availability and increase plant P uptake in this acidic paddy soil where P is not the limiting factor.